The Capability Of Gigantochloa Scortechinii Bamboo As Sound Absorber - Kamisan, Ifa Shafiqa (Universiti Sains Malaysia, 2022)
Noise, to put it simply, is unwanted sound. Sound is a kind of energy that is released by a vibrating medium and provides the sensation of hearing when it reaches the ear via nerves. This research provides an overview and description of the physical properties of materials such as fiber size, the presence of resin and the use of an air gap behind the specimen on the bamboo fiber capacity to absorb sound. The samples were fabricated from raw Gigantochloa Scortechinii bamboo fibers with different fiber diameter and air gap layer behind the samples to observe their effects on sound absorption characteristic. The morphology images of the samples were analyzed using Scanning Electronic Microscope (SEM) and Impedance Tube based on ISO 10534-2:1998. Results from the experimental tests show that bamboo fiber has good acoustic properties at high frequencies and can be used as an alternative replacement to conventional product. It reveals that the sound absorption of bamboo fibers with presence of epoxy resin was found has a better performance compared to the samples without resin. The fiber size of 850 μm bamboo fiber diameter achieves sound absorption coefficient of 0.47 at a frequency 700 Hz which is below 0.5 which is shows a poor performance. The increasing of the air gap does not affect the performance of the bamboo sample. From the study, the performance of the bamboo was categorized based on the range of sound absorption coefficient which is below 0.5 was performed a poor performance while above 0.5 is consider has a better performance. Thus, the sound absorption of Gigantochloa Scortechinii bamboo was experimentally tested and proven to be effective.